Cultures Within National Cultures: International Marketing Within the Domestic Marketing Environment - Rasha Y Tantawy; Babu P George (Economic Review: Journal of Economics and Business, 2016)
As a result of increasing multiculturalism within countries, even traditionally domestic marketers are beginning to experience similar environmental conditions that were once exclusive to their international marketing counterparts. It would be interesting to examine how groups within the same domestic environments acquire different consumption habits. This study explores consumption patterns in developing countries that result in the adoption of products, services, and consumption practices originating from several other cultures. This and related issues are discussed in the context of four countries, Turkey,Egypt, Singapore, and Nigeria that are dispersed geographically, diverse in cultures, yet similar in their openness to the world and their economic growth. The study identifies three types of culture interpenetrations and four major causes accelerating the change; globalization, technology, media, mobility, and demographics.
Keywords: G32; 330; globalization; multicultural environment; culture patterns; consumption behavior; marketing; developing countries